2013
DOI: 10.11648/j.ajbio.20130102.12
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Biochemical Compositions and Mineral Contents of Carapace of Some Important Commercially Crustaceans and Mollusks Organisms from Egyptian and Saudi Arabia Coasts as a New Animal Feed

Abstract: Abstract:Carapace of commercial crustaceans species (mantis shrimps ; Erugosquilla. massavensis, the penaeid shrimps ; Peaneus. semisulcatus ; Metapenaeus monoceros and blue crab; Portunus pelagicus ) and commercial mollusks (cuttlefish ; Sepia and bivalve mollusks; Cardium edule) were chosen for this study to assess carbohydrates, protein, lipids and to estimate their Fe, Cu, Co, Hg, Pb and Cd contents, as an attempt to use the carapace of marine invertebrates organisms as a cheap protein animal feed. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…An important consideration is that the shell contamination with particular metals strongly depends on the type of local environmental pollution from industrial effluent [ 22 , 23 ]. Similar, or slightly lower range of Fe, Cu, Pb, and Cd content than in the present study, was reported by Abdel-Salam [ 24 ] in the shell of several crab species, who suggested that the shells of respective species originating from Egyptian and Saudi Arabia coasts are suitable for use as mineral supplements for animal feed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An important consideration is that the shell contamination with particular metals strongly depends on the type of local environmental pollution from industrial effluent [ 22 , 23 ]. Similar, or slightly lower range of Fe, Cu, Pb, and Cd content than in the present study, was reported by Abdel-Salam [ 24 ] in the shell of several crab species, who suggested that the shells of respective species originating from Egyptian and Saudi Arabia coasts are suitable for use as mineral supplements for animal feed.…”
Section: Discussionsupporting
confidence: 91%
“…This means that the crab shells like these considered here would have to be combined with another As- and Cd-free fertilizing material to reduce the content of the contaminants per unit of weight. Nevertheless, the content of other contaminants, such as Pb, Ni, Zn, Cu, and Cr (VI), is commonly 1 to 3 orders of magnitude below the legal threshold, as also evidenced by Abdel-Salam [ 24 ], still making the crab shells an attractive naturally sourced composite material for agricultural applications.…”
Section: Discussionmentioning
confidence: 99%
“…The observed TEAA/TAA ratios for Crab, Periwinkle, and Oyster were 0.5, which showed that they have good quality proteins and might support protein synthesis [19]. In this study, the results for TEAAs/TNEAAs ratios were in tandem with the ones reported by Abdel-Salem [21], that the ratio of TEAAs/TNEAAs ranged between 0.7 -1.09. Branched-chain amino acids (BCAAs) are required for protein synthesis, repair, and maintenance of the muscle tissues.…”
Section: Amino Acid Levels In the Seafood Samplessupporting
confidence: 84%
“…In addition to, these essential metals appear to diffuse passively probably as a soluble complex by the gradients created through adsorption of membrane surface [40]. In comparison with bioaccumulation of Fe, Cu, Co, Hg, Pb and Cd in carapaces of these studied species in the previous study [21] it was detected that carapaces of determined crustaceans and mollusks species had higher contents of essential and non-essential heavy metals than in their edible muscles. From these results, it is suggested that shell of marine organisms may be behave as an indicator of changes in environmental pollution, presenting a lower variability compared with soft tissue and providing a historical record of metal content in the body throughout its life cycle as attributed by [48].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the bioaccumulation studies led to adoption of the bioindicators concept. Seafood is widely used as bioindicators of marine pollution by metals [20,21]. The use of marine organisms as bioindicators of metal pollution of aquatic environments and suitability for human use from toxicological point has been documented [9, 13-15, 22, 23 ] .…”
Section: Introductionmentioning
confidence: 99%